Using PCR technique for diagnosis of bacterium Escherichia coli O157:H7 isolated from urine samples of humans and sheep: Al-wgaa, A. A.@ and Alwan, M. J. - A., Al-wgaa A. (The Iraqi Journal of Veterinary Medicine, 2014)
The aims of the current study were to determine the percentages of E.coli O157:H7 in the urinary tract infections (UTIs) of humans and in the urine of apparently healthy sheep, in addition to determine the genotype of the isolates by PCR assay. Two hundred and twenty eight urine samples were collected from young children and adult patients both sexes suffering from UTIs during a period December 2012 to the end of March 2013. And randomly collected 75 urine sample from apparent healthy sheep both sexes that were slaughtered in AL Shoela, AL Rahmanea Slaughterhouse and College of Veterinary Medicine field in Baghdad the end of February to half of April 2013. All urine samples were incubated aerobically at 37°C for 24-48 hrs on blood agar, MacConkey agar as well as special media and the isolates were identified by biochemical tests, then the isolates were confirmed diagnosed by PCR assay. The results showed that humans urine samples ,8 samples were E. coli O157:H7 positive isolates(3.50%) ,young children expressed (4) isolates of E.coli O157:H7 as compare with those in adult (4 isolates) and the percentage of this isolates in females were (2.6%) as compare with those in males (0.87%). Also the current study demonstrated that all isolates culturing positive serotype of E.coliO 157:H7 were positive by PCR assay .The genes of eaeA ,hly and Stx2 were recorded in 7,8 and 2 serotype of E.coliO157:H7 respectively. The result revealed that 21(28%) out 75 sheep urine samples were E.coli positive isolates, 13 out 75 samples were E.coli O157:H7 positive isolates. The percentage of isolates from rams urine samples was (14.66%) as it compare to those samples of ewes (2.66%).The result also was recorded that 10,13,12,4 and 3 of bacterial isolates of sheep urine samples were carried eaeA, hlyA, hlyA plasmid,Stx1 and Stx2 genes respectively. In conclusion the healthy sheep in Baghdad city, harbor shiga -toxin producing E.coliO157:H7 in their urinary tracts and these organism induced UTIs associated with renal failure in the humans and carried the same virulent genes that reported in the sheep isolates.